LINC01189-miR-586-ZEB1 feedback loop regulates breast cancer progression through Wnt/β-catenin signaling pathway - Di Zhang; Xiaofeng Liu; Yun Li; Li Sun; Shu-Shu Liu; Yue Ma; Huan Zhang; Xin Wang; Yue Yu (Elsevier, 2021)
Non-coding RNAs play essential roles in breast cancer progression by regulating proliferation, differentiation, invasion, and metastasis. However, our understanding of most microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) in breast cancer is still limited. miR-586 has been identified as an important factor in the progression of some types of cancer, but its exact function and relative regulation mechanisms in breast cancer development need to be further investigated. In this study, we showed miR-586 functioned as an oncogene by promoting breast cancer proliferation and metastasis both in vitro and in vivo. Meanwhile, miR-586 induced Wnt/β-catenin activation by directly targeting Wnt/β-catenin signaling antagonists SFRP1 and DKK2/3. Moreover, we demonstrated that LINC01189 functioned as a tumor suppressor and inhibited breast cancer progression through inhibiting an epithelial-mesenchymal transition (EMT)-like phenotype by sponging miR-586. In addition, β-catenin/TCF4 transactivated ZEB1, resulting in a transcriptional repression of LINC01189 expression. In conclusion, our data uncovered the LINC01189-miR-586-ZEB1 feedback loop and provided a novel mechanism participating in the regulation of Wnt/β-catenin signaling in breast cancer progression.